Youth Permanent Part-Time Employment as a Labour Market Alternative to Full Time Work: A Longitudinal Analysis - Joseph A. Raelin (Journal of Occupational Behaviour, 1983)
This study examines two hypotheses developed from the literature on part-time employment that youth whose first job becomes permanent and who are employed part-time will experience neither lower status nor wages in their later work experience compared to their full-time counterparts. These same youth, however, will not fare as well in their later employment compared to in-school youth who are also working part-time. The data, which are taken from independent samples of the National Longitudinal Surveys (NLS), are subjected to analyses of variance and covariance. The latter technique adjusts the main effects of working time for a number of work experience and demographic variables which were identified as potential contaminants. The results support both hypotheses. Permanent part-time work for youth who choose not to remain in school is a viable labour market alternative. The policy implications of this general finding are discussed.
Keywords: E24; J13; 330; part-time employment; youth employment